The bridge on the River Kwai [videorecording (Blu-Ray)] - Guinness, Alec, 1914-2000; Holden, William, 1918-1981; Hawkins, Jack, 1910-1973; Hayakawa, Sesshū, 1889-1973; Foreman, Carl; Wilson, Michael, 1914-1978; Spiegel, Sam; Lean, David, 1908-1991; Boulle, Pierre, 1912-1994 (Sony Pictures Home Entertainment, 2011)
British POWs are forced to build a railway bridge for their WWII Japanese captors, unaware of an Allied mission to blow it up.